Industrial Clustering: A Case Study On The MSC Cluster In Malaysia - Cheong, Jin Shi (2008)
In this case study, we will feature Cyberjaya's MSC, which is an example of a local cluster focusing on ICT. Unlike Silikon Valley which was developed naturally over a span of half a century, this cluster was formed from the result of conscious and deliberate Government policy and effort.